Picture Series in Teaching Writing Skills: A Literature Review - Erniwati Erniwati; Sudarkam Ramlan Mertosono; Rofiqoh Rofiqoh; Rasni Ahmad Gente (Premise: Journal of English Education and Applied Linguistics, 2022)
This library research investigates how picture series implementation effectively improves students' writing skills on different text types. Data were collected from journals published in the last ten years, from 2012-2022, and analyzed using content analysis. The results indicated that picture series effectively improve students' writing skills in descriptive, narrative, recount, procedure, explanation, and spoof texts. Even the picture series is helpful when applied to teach writing skills to deaf and hard-of-hearing students. A visual representation of events arranged in chronological order naturally provides the students with clues that can help them arrange and develop ideas in writing. Besides, the picture series stimulate the students' process of thinking and imagination to write the assigned text. Picture series also promote students' engagement and participation. In other words, picture series enables students to improve their writing skills and change their behavior toward learning.